2017
DOI: 10.12659/msm.900856
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of High-Sensitivity C-Reactive Protein, Procalcitonin and Pancreatic Stone Protein in Pediatric Sepsis

Abstract: BackgroundTo investigate the prognostic value of procalcitonin (PCT), high-sensitivity C-reactive protein (hs-CRP), and pancreatic stone protein (PSP) in children with sepsis.Material/MethodsA total of 214 patients with sepsis during hospitalization were enrolled. Serum levels of PCT, hs-CRP, and PSP were measured on day 1 of hospitalization and the survival rates of children were recorded after a follow-up of 28 days. Pearson’s correlation analysis was conducted to test the association of PCT, hs-CRP, and PSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…High-sensitivity C-reactive protein (hs-CRP), a key inflammatory cytokine, has been found to be an early marker of sepsis severity and poor prognosis in a few studies in children with sepsis. 25 We performed a dynamic assessment of hs-CRP and found that nonsurvivors persisted to have high hs-CRP. The strengths of our study include its practical applicability in the emergency settings rather than ICUs, which are often scant in resource poor countries.…”
Section: Discussionmentioning
confidence: 99%
“…High-sensitivity C-reactive protein (hs-CRP), a key inflammatory cytokine, has been found to be an early marker of sepsis severity and poor prognosis in a few studies in children with sepsis. 25 We performed a dynamic assessment of hs-CRP and found that nonsurvivors persisted to have high hs-CRP. The strengths of our study include its practical applicability in the emergency settings rather than ICUs, which are often scant in resource poor countries.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the large population in China, sepsis will be a great threat to people's life and a heavy burden on the health care system. Therefore, early identi cation and timely prevention will undoubtedly improve the prognosis of patients with sepsis [41] Researches showed that multiple factors, including patient admission scores, patients comorbid disease and demographic indicators like age, gender, race, were capable of affecting the prognosis of patients with sepsis, accompanied by numerous laboratory indexes such as neutrophil to lymphocyte ratio, platelet, albumin, procalcitonin, C-reactive protein, creatinine, urea nitrogen and lactate [38,39,[42][43][44][45][46][47] . Continuous monitoring of these indicators is conducive to early identi cation and timely treatment of septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is one of the main causes of death in patients after ineffective and untimely antibiotic therapy, fulminant infections, superinfection, inadequate diagnosis of the patient's condition, risky surgeries performed in violation of asepsis standards, or the appearance and spreading of a wound infection [2]. The generalization of the process, resulting in the disruption of the biochemical functions of vital organs and the appearance of local foci of inflammation, leads ultimately to the inability of the organism to fight bacterial infection, leading to severe septicemia, intoxication of the organism with the decay products of pathogens and its own tissues, septic shock and multi-organ failure [38]. A schematic representation of the mechanism is shown in Figure 2.…”
Section: Markers Of Inflammatory Processes and Choice Of Bacterial Inmentioning
confidence: 99%
“…For example, Miglietta et al [44] showed that procalcitonin is found in high concentrations in the blood at the early stages of sepsis, and its content only decreases after intensive antibiotic therapy. The work of Wu et al demonstrated the prognostic role of procalcitonin, since high levels of this marker were subsequently associated with the death of patients, while, in the surviving group, its content in the blood was lower [38]. However, the decisive factor in choosing this marker as an indicator of the presence of septic process due to bacterial infection is its important distinguishing feature-unlike other markers of inflammation, procalcitonin level never rises if the infection process has a viral etiology [45].…”
Section: Concentration Of Procalcitonin In Blood During Development Omentioning
confidence: 99%
See 1 more Smart Citation